Family Cluster of Middle East Respiratory Syndrome Coronavirus Infections - Memish, Ziad A; Zumla, Alimuddin I; Al-Hakeem, Rafat F; Al-Rabeeah, Abdullah A; Stephens, Gwen M (The New England journal of medicine, 2013)
A novel coronavirus (MERS-CoV) was recently identified as the cause of severe respiratory disease. In this report from Saudi Arabia, a family cluster of infection over a 6-week period is described, suggesting possible limited person-to-person transmission. MERS-CoV was first reported in September 2012 in samples obtained from a Saudi Arabian businessman who died from acute respiratory and renal failure. 1 As of May 28, 2013, a total of 49 cases of human MERS-CoV infection with 26 deaths have been reported to the World Health Organization (WHO). MERS-CoV is the first betacoronavirus belonging to lineage C that is known to infect humans. 2 It belongs to the Coronaviridae family, a group of large, enveloped single-stranded RNA viruses that are known for their genomic plasticity and their ability to cause a range of infections in mammalian and avian hosts. MERS-CoV . . .